Long-latency reflexes account for limb biomechanics through several supraspinal pathways - Kurtzer, Isaac L. (Frontiers in Integrative Neuroscience, 2015)
Accurate control of body posture is enforced by a multitude of corrective actions operating over a range of time scales. The earliest correction is the short-latency reflex which occurs between 20-45 ms following a sudden displacement of the limb and is generated entirely by spinal circuits. In contrast, voluntary reactions are generated by a highly distributed network but at a significantly longer delay after stimulus onset (greater than 100 ms). Between these two epochs is the long-latency reflex (around 50-100 ms) which but acts more rapidly than of voluntary reactions but shares some supraspinal pathways and functional capabilities. In particular, the long-latency reflex accounts for the arm’s biomechanical properties rather than only responding to local muscle stretch like the short-latency reflex. This paper will review how the long-latency reflex accounts for the arm’s biomechanical properties and the supraspinal pathways supporting this ability. Relevant experimental paradigms include clinical studies, non-invasive brain stimulation, neural recordings in monkeys, and human behavioral studies. The sum of this effort indicates that primary motor cortex and reticular formation contribute to the the long-latency reflex either by generating or scaling its structured response appropriate for the arm’s biomechanics whereas the cerebellum scales the magnitude of the feedback response. Additional putative pathways are discussed as well as potential research lines.